M. Fethullah Gülen's Blueprint for World Peace - Richard Penaskovic (Journal of Global Initiatives, 2010)
This article attempts to sift through the writings of Fethullah Gülen) a Turkish intellectual) in order to make explicit his blueprint for world peace. Gülen argues that today)s world has succumbed to materialism and hedonism. The antidote consists in the development of one)s interior or spiritual life) adorning oneself with such virtues as humility) love) and self-sacrifice. He also calls for an education that involves the whole person: body) mind) and spirit. Acceptance of others and dialogue between East and West) Muslims and Christians is essential if there is to be peace on earth.